ANALISIS BALANCED SCORECARD DALAM RANGKA MENGUKUR KINERJA PERUSAHAAN PADA PT PAN INDONESIA Tbk PANGKALPINANG - Maria; Tri Setyo Mulyani, Hendarti; Zamhari (Jurnal Akuntansi Bisnis Dan Keuangan, 2024)
This research employs a descriptive quantitative approach, using primary and secondary data collected through interviews, questionnaires, and company documentation. The collected data were analyzed using statistical analysis techniques to measure each perspective of the Balanced Scorecard. The research results indicate that PT PAN Indonesia Tbk Pangkalpinang has good performance in the financial perspective, as evidenced by consistent increases in revenue and profitability. However, there are several areas needing further attention, such as cost utilization and maximizing product sales. The customer perspective also shows positive results, with a high level of customer satisfaction. The internal process perspective indicates that the company is capable of implementing innovation and operational processes to meet customer needs, such as product innovation and product distribution to customers. The growth and learning perspective shows that the company is able to maintain employee welfare and provide employee satisfaction, such as optimizing operational efficiency and providing training programs to employees. Overall, the implementation of the Balanced Scorecard at PT PAN Indonesia Tbk Pangkalpinang provides a more holistic view of the company’s performance and assists management in formulating strategies for continuous improvement.